SIMPLIFIED GRAPHICAL DOMAIN-SPECIFIC LANGUAGES FOR THE MOBILE DOMAIN – PERSPECTIVES OF LEARNABILITY BY NONTECHNICAL USERS - ŻYŁA, Kamil (Applied Computer Science, 2017)
Increasing number of technologically advanced mobile devices causes the need for seeking methods of software development that would involve persons without or with highly limited programming skills. They could participate as domain experts or individual creators of personal applications. Methods based on models might be the right answer, thus the author conducted workshops and surveys concerning perspectives of graphical modeling languages for the mobile domain. Research revealed that nontechnical users declared high learnability of simplified ones as well as the majority of them correctly read models in such languages.